The effect of badminton-specific exercise on badminton short-serve performance in competition and practice climates. Issue 2 (7th February 2017) - Duncan, Michael J.; Chan, Cheryl K.Y.; Clarke, Neil D.; Cox, Martin; Smith, Mike
Abstract: This study examined the effects of changes in physiological and psychological arousal on badminton short-serve performance in competitive and practice climates. Twenty competitive badminton players (10 males and 10 females) volunteered to participate in the study following ethics approval. After familiarisation, badminton short-serve performance was measured at rest, mid-way through and at the end of a badminton-specific exercise protocol in two conditions; competition vs. practice. Ratings of cognitive and somatic anxiety were assessed at three time points prior to badminton short-serve performance using the Mental Readiness Form 3. Heart rate and rating of perceived exertion (RPE) were assessed during the exercise protocol. Results indicated that better short-serve performance was evident in practice compared to competition ( P = .034). RPE values were significantly higher in the competition condition compared to practice ( P = .007). Cognitive anxiety intensity was significantly lower post-exercise in the practice condition compared to competition ( P = .001). Cognitive anxiety direction showed greater debilitation post-exercise in the competition condition compared to practice ( P = .01). Somatic anxiety intensity increased from pre-, to mid- to post-exercise ( P = .001) irrespective of condition. This study suggests that badminton serve performance is negatively affected when physiological arousal, via badminton-specific exercise, and cognitive anxiety, via perceived competition, are high.